ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EKSPOR BIJI PALA INDONESIA - Sayidah, Anis; Iskandar, Sutarmo; Iswarini, Harniatun (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2014)
This study aim to find out how the free on board nutmeg price factor, U.S dollar exchange rate and lag of nutmeg export volume influence nutmeg export, to find out the trend of nutmeg export volume ten years later. This reasearch has been carried out by taking secondary data about the nutmeg in the central bureau statistic and the relavan deparment. Data collection time was conducted in November-January 2014. The reasearch method used in this reasearch secondary data method, data collection methods used are secondary data (time series). Processing and data analysis method affect the nutmeg export volume is used multiple linear regression analysis, to find out the trend of nutmeg export volume is used least squere trend analysis. The result showed that the variables free on board price of nutmeg, U.S dollar exchange rate, and lag of nutmeg export together have significant influence to Indonesian nutmeg export volume. Partially free on board price of nutmeg variable has a significant influence on the volume of nutmeg export. As for the U.S dollar exchange rate and lag of nutmeg export volume non significant effect on the volume of Indonesian nutmeg export. As for result of the nutmeg export trend from 2002-2022 showed that demand of Indonesian nutmeg export is positive, it mean that Indonesian nutmeg export volume increased from year to year.